La tarification et la sélection des risques - Lemieux, Claude (Assurances)

(untitled) (HEC Montréal, 1988)
First, Mr. Claude Lemieux puts forward the factors which are liable to affect the mortality rate and the role of the underwriters, using scientific data and a great deal of good judgement. Second, he looks at the AIDS problem and at its implications as an insurance risk. For example, he examines the problem of more stringent selection standards.